PEMANFAATAN KETAN HITAM DALAM PEMBUATAN KOPI BUBUK - Muharram, Rezqy; Yusmarini, Yusmarini; Harun, Noviar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to obtain precise ratio between coffee bean and black sticky rice to reach result the most preferred coffee by panelists and comply standard quality of coffee product. This research used a Complete Randomized Design (CRD) with 5 treatments and 3 replications. The Treatments were BKKH0 (100% Coffee), BKKH1(90% Coffee and 10% Black sticky Rice) BKKH2 (80% Coffee and 20% Black sticky Rice), BKKH3 (70% Coffee and 30% Black sticky rice), BKKH4 (60% Coffee and 40% Black sticky rice). The Collected Data was analyzed statistically with analysis of variance (ANOVA) and Duncan’s New Multiple Range Test (DNMRT) at 5% stage. The research showed, the application of coffee and black sticky rice had significant effect to water content, ash content, antioxidant content, caffeine content and organoleptic test. The best treatment  of this research was treatment BKKH4 which had a water content 4,23%; ash content 3,51%; antioxidant content 12,60 µg/ml, and caffeine content 1,24%. It was described as brown coloured and coffee scent for it’s powder, then black coloured and had coffee scent for the coffee. It was also the most preffered by panelists according the over all assessment.Keywords : Coffee powder, coffee bean, and black sticky rice.